Superiority of Roeder's Knot for Fascial Mesh Fixation in a Cadaveric Model. (August 2017) - Fanous, Medhat; Warren, Jeremy; Cobb, William
Objective . This study compares the use of Roeder's knot (1:3:1, 1 hitch, 3 winds, and 1 locking hitch) to the surgeon's knot regarding the security of the knot and predictability of its position. Method . A polypropylene mesh was secured to the undersurface of the abdominal wall of a fresh frozen cadaver using tacks. Eight standardized transfascial sutures were performed. Four of them were secured with surgeon's knot and the remaining 4 were tied with Roeder's knot. A Mosquito hemostat was placed between the mesh and the stitch loop and the distance between its jaws was measured. We then created subcutaneous flap and measured the vertical distance between the knot and the anterior sheath. Results . When surgeon's knot was used, the distance between the mesh and the stitch loop ranged between 4 and 6 mm. This distance could not be measured when Roeder's knot was used due to inability to place hemostat between the mesh and the stitch loop. The vertical length between the anterior sheath and the surgeon knot ranged between 3 and 13 mm while remaining consistent at 2 mm when Roeder's knot was applied. Conclusions . This study shows that Roeder's knot is superior to the regular sliding knot in securing the mesh to the abdominal wall. It can be tightened appropriately and leads to less variation when used properly. It has many other applications that stem from its ability to be advanced with different degrees of tightness based on body habitus and the operative requirements.